Development of a novel hyaluronic acid membrane for the treatment of ocular surface diseases - Dong Ju Kim; Mi-Young Jung; Ha-Jin Pak; Joo-Hee Park; Martha Kim; Roy S. Chuck; Choul Yong Park (Scientific Reports, 2021)
Abstract Ocular surface diseases (OSD) can cause serious visual deterioration and discomfort. Commercial artificial tear solution containing hyaluronic acid (HA) show excellent biocompatibility and unique viscoelastic characteristics. Here, we developed a novel HA membrane (HAM) by chemical crosslinking using 1,4-butanediol diglycidyl ether for the effective treatment of OSDs. The main purpose of HAMs is to provide sustained release of HA to modulate the wound healing response in OSDs. The safety and efficacy of HAMs were investigated using primary cultured human corneal epithelial cells and various OSD rabbit models. In the dry state, the HAM is firm, transparent, and easy to manipulate. When hydrated, it swells rapidly with high water retention and over 90% transmission of visible light. Human corneal epithelial cells and rabbit eyes showed no toxic response to HAM. Addition of HAMs to the culture medium enhanced human corneal epithelial cell viability and expression of cell proliferation markers. Investigation of HAM wound healing efficacy using mechanical or chemical corneal trauma and conjunctival surgery in rabbits revealed that application of HAMs to the ocular surface enhanced healing of corneal epithelium and reduced corneal limbal vascularization, opacity and conjunctival fibrosis. The therapeutic potential of HAMs in various OSDs was successfully demonstrated.